2019
DOI: 10.1155/2019/4121234
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Grey Zone Lymphoma Successfully Treated with Brentuximab Vedotin and R-CHP Chemotherapy

Abstract: Introduction. The diagnosis of B-cell lymphoma, unclassifiable, with features intermediate between diffuse large B-cell lymphoma (DLBCL) and classical Hodgkin’s lymphoma (cHL), also referred to as grey zone lymphoma (GZL), is a challenging diagnosis. There are no standardized guidelines; however, evidence strongly suggests that DLBCL-based regimens are effective in the treatment of GZL. Brentuximab vedotin (BV) is an anti-CD30 antibody drug conjugate that has established efficacy in relapsed/refractory Hodgkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Extensive study of histological changes is indispensible for even an experienced hematologist hence core biopsy sampling often has limited value in the diagnosis of GZL, and excision of the complete lymph node is preferred. What may alert the pathologist is the contrasting morphological and immunohistological pictures, which can warrant detailed study, possibly further immunostaining or indicate repeated sampling [6][7][8]. In our patients the two patterns could be clearly distinguished with initial DLBCL morphology in 6 cases and cHL (morphology) in 3.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Extensive study of histological changes is indispensible for even an experienced hematologist hence core biopsy sampling often has limited value in the diagnosis of GZL, and excision of the complete lymph node is preferred. What may alert the pathologist is the contrasting morphological and immunohistological pictures, which can warrant detailed study, possibly further immunostaining or indicate repeated sampling [6][7][8]. In our patients the two patterns could be clearly distinguished with initial DLBCL morphology in 6 cases and cHL (morphology) in 3.…”
Section: Discussionmentioning
confidence: 60%
“…The disease can be managed using DLBCL-type (R-CHOP, DA-EPOCH-R), or cHL-type (ABVD, escBEACOPP) protocols. Literature data and studies with larger numbers of cases show that DLBCL-type treatments appear to be more effective [3][4][5][6][7][8]. However, experts' opinions on the use of rituximab are less clear: while Evens et al [3] found therapies with additional rituximab more favourable in terms of progression-free survival, Sarkozy et al [5] did not find rituximab-containing protocols more favourable either for event-free or for overall survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we report the case of a patient with GZL, which is rare in Asian populations[ 6 - 9 ], who was successfully treated with cyclophosphamide, doxorubicin, vincristine, prednisolone, and rituximab (R-CHOP) chemotherapy.…”
Section: Introductionmentioning
confidence: 99%